The Impact of the Window Orientation on Natural Ventilation and Energy Consumption (Case of Collective Housing in Laghouat City) - Khadidja Dohsi; Hamida Bencheikh (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Natural ventilation still one of the most basic elements of thermal comfort in the building to ensure cooling and air renewal of internal spaces, especially in the residential sector. With the concern for the unsustainability of fossil and non-renewable energies and the gradual rise of housing demand in Algeria, energy conservation has become a major issue, especially in the arid regions of the country such as Laghouat City. This motivated us to study the ventilation and its correlation with the window orientation, so we hypothesized that the orientation of the window has an important effect on natural ventilation and energy consumption. In order to verify our hypothesis, we used the computational analysis with Energyplus 8.4 software for obtaining the interior space temperatures for each orientation as well as the energy consumption of electricity and gas, and then comparing them to determine the most advantageous orientation to have a well-ventilated space with a low energetic consumption.